The Quran's Universal Perspective on Dialogue of Religions and Civilizations and Islam's Theological Foundation of Peaceful Coexistence - Bakar, Osman (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Quran's Universal Perspective on Dialogue of Religions and Civilizations and Islam's Theological Foundation of Peaceful Coexistence